Teknologimorfosis Evolusi Teknologi dalam Masyarakat Digital - Prabu Revolusi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The development of digital technology has brought significant changes in human life, transforming the way we interact, work, and transact. The concept of Technomorphosis becomes crucial as a theoretical framework to understand the technological transformation occurring in the digital society. Inspired by the Media Morphosis theory developed by Roger Fidler, Technomorphosis explains that the evolution of technology does not entirely replace old technologies, but rather adapts and transforms elements from previous technologies. This process involves four main principles: inheritance, convergence, persistence, and acceleration, which reflect the dynamics of technological change in the interconnected digital ecosystem. This research uses a conceptual theory approach and descriptive qualitative methodology to explore how technological transformation occurs within social and cultural contexts. The case studies discussed include technological phenomena such as digital platforms, mobile devices, and artificial intelligence, which illustrate the principles of Technomorphosis in practice. This research emphasizes the importance of a deeper understanding of the dynamics of technological transformation, focusing on the role of humans in the ever-evolving technology ecosystem. With the rapid advancement of technology in the digital age, society is becoming increasingly dependent on information and communication technology in everyday life. By introducing the concept of Technomorphosis, this research aims to provide new insights into understanding these changes, as well as the challenges and opportunities that arise in the future of an increasingly digitally connected society.